Crop breeding for a changing climate in the Pannonian region: towards integration of modern phenotyping tools. (10th May 2022) - Kondić-Špika, Ankica; Mikić, Sanja; Mirosavljević, Milan; Trkulja, Dragana; Marjanović Jeromela, Ana; Rajković, Dragana; Radanović, Aleksandra; Cvejić, Sandra; Glogovac, Svetlana; Dodig, Dejan; Božinović, Sofija; Šatović, Zlatko; et al.
Abstract : Different phenotyping methods used in the Pannonian region to evaluate complex traits related to growth, yield, quality, and adaptation of crops to different environmental stresses are presented. Abstract: The Pannonian Plain, as the most productive region of Southeast Europe, has a long tradition of agronomic production as well as agronomic research and plant breeding. Many research institutions from the agri-food sector of this region have a significant impact on agriculture. Their well-developed and fruitful breeding programmes resulted in productive crop varieties highly adapted to the specific regional environmental conditions. Rapid climatic changes that occurred during the last decades led to even more investigations of complex interactions between plants and their environments and the creation of climate-smart and resilient crops. Plant phenotyping is an essential part of botanical, biological, agronomic, physiological, biochemical, genetic, and other omics approaches. Phenotyping tools and applied methods differ among these disciplines, but all of them are used to evaluate and measure complex traits related to growth, yield, quality, and adaptation to different environmental stresses (biotic and abiotic). During almost a century-long period of plant breeding in the Pannonian region, plant phenotyping methods have changed, from simple measurements in the field to modern plant phenotyping and high-throughput non-invasive and digital technologies. In this review, we present a short historical background and the most recent developments in the field of plant phenotyping, as well as the results accomplished so far in Croatia, Hungary, and Serbia. Current status and perspectives for further simultaneous regional development and modernization of plant phenotyping are also discussed.